Molecular Coupling of Histone Crotonylation and Active Transcription by AF9 YEATS Domain - Li, Yuanyuan; Sabari, Benjamin R.; Panchenko, Tatyana; Wen, Hong; Zhao, Dan; Guan, Haipeng; Wan, Liling; Huang, He; Tang, Zhanyun; Zhao, Yingming; Roeder, Robert G.; Shi, Xiaobing; et al. (Molecular cell, 2016)
Recognition of histone covalent modifications by chromatin-binding protein modules (“readers”) constitutes a major mechanism for epigenetic regulation, typified by bromodomains that bind acetyllysine. Non-acetyl histone lysine acylations (e.g., crotonylation, butyrylation, propionylation) have been recently identified, but readers that prefer these acylations have not been characterized. Here we report that the AF9 YEATS domain displays selectively higher binding affinity for crotonyllysine over acetyllysine. Structural studies revealed an extended aromatic sandwiching cage with crotonyl specificity arising from π-aromatic and hydrophobic interactions between crotonyl and aromatic rings. These features are conserved among the YEATS, but not the bromodomains. Using a cell-based model, we showed that AF9 co-localizes with crotonylated histone H3 and positively regulates gene expression in a YEATS domain-dependent manner. Our studies define the evolutionarily conserved YEATS domain as a family of crotonyllysine readers and specifically demonstrate that the YEATS domain of AF9 directly links histone crotonylation to active transcription. [Display omitted] •The YEATS domains constitute a family of histone crotonylation reader modules•AF9 YEATS recognizes histone crotonylation via an extended aromatic sandwich pocket•Bromodomains do not exhibit YEATS-like preference for crotonyllysine•Histone crotonylation potentiates gene expression in an AF9 YEATS-dependent manner Li et al. demonstrate that the YEATS domain has an expanded acyl-binding repertoire with highest preference for crotonyllysine. The AF9 YEATS-crotonyllysine interaction is critical for histone crotonylation-dependent gene activation in the context of the inflammatory response.